2019
DOI: 10.5430/ijfr.v10n3p11
|View full text |Cite
|
Sign up to set email alerts
|

Board Capabilities and the Mediating Roles of Absorptive Capacity on Environmental Social and Governance (ESG) Practices

Abstract: Public listed companies in Malaysia have been pressured tremendously to accept the engagement of Environment, Social and Governance (ESG), but the engagement is still low based on previous studies. ESG will enhance company financial performance, image as well as the ability to attract and retain the workplace which contributes to the market value in the economy. This shows that ESG engagement improve company brand image and reputation, increase customer loyalty and sales as well as productivity. Corporate gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…These results are similar to research (Birindelli et al, 2018) and (Ismail et al, 2019) where the presence of an independent director of a company can increase the value of the ESG score because it adds social and economic credibility to the company so that corporate image also gets better (Romano et al, 2020). Independent directors tend to pay more attention to the welfare and environmental activities and usually have a broader perspective than the interests of shareholders.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…These results are similar to research (Birindelli et al, 2018) and (Ismail et al, 2019) where the presence of an independent director of a company can increase the value of the ESG score because it adds social and economic credibility to the company so that corporate image also gets better (Romano et al, 2020). Independent directors tend to pay more attention to the welfare and environmental activities and usually have a broader perspective than the interests of shareholders.…”
Section: Resultssupporting
confidence: 80%
“…Board independence tends to produce better results in decision-making, resulting in improved corporate governance and oversight (Ismail et al, 2019). Consequently, the independence of the board of directors can improve the performance and value of the enterprise in implementing its sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…This framework acknowledges that businesses should not be evaluated solely on economic indicators but also on their impact on the environment, society, and their governance practices (Eccles et al, 2020). The origins of ESG can be traced back to earlier concepts such as Socially governance (Ismail et al, 2019). Two studies (Chouaibi & Chouaibi, 2021;Sandberg et al, 2023) examine the relationship between ESG factors and financial performance across different industries.…”
Section: B) Scientific Productions and Citations Over Timementioning
confidence: 99%
“…Aliyu (2019), in his study, indicated a significant positive relationship between board independence, board meetings, and corporate environmental reporting. Also, Ismail et al (2019) argue that the current global and innovative economy considers social and environmental issues comprising income distribution and growth. The board plays a crucial role in ensuring that companies engage with environmental and social governance practices that can enhance value addition and financial p e r f o r m a n c e .…”
Section: Review Of Literaturementioning
confidence: 99%